DESCRIPTION OF THE ADMINISTRATION OF BOILED MORINGA LEAVES TO REDUCE RANDOM BLOOD GLUCOSE LEVELS IN MRS. D WITH TYPE 2 DIABETES MELLITUS IN SIKAMPUH VILLAGE, KROYA DISTRICT, CILACAP REGENCY - Latifah Azhar Dini; Eko Julianto; Sudiarto; Dwi Astuti (PT. Jurnal Center Indonesia Publisher, 2026)
Background: Diabetes mellitus is a chronic metabolic disorder caused by high levels of physical activity, high sugar consumption, reduced insulin production, and impaired insulin response or other hormones that inhibit insulin action. Based on IDF data, the prevalence of diabetes mellitus in Indonesia in 2024 is estimated to reach 11.3% of the population (approximately 20.4 million people). In addition, the Ministry of Health shows that in 2023, cases of diabetes mellitus will reach 11.7% and are predicted to continue to increase. High blood glucose levels, if left untreated, can cause various complications such as heart disease, stroke, nerve damage, and wound infections that can lead to amputation. One non-pharmacological treatment that can be given is by giving boiled moringa leaves, because moringa leaves contain antioxidants such as flavonoids, vitamins A, C, and E which can lower blood glucose levels. Objective: To determine the effect of Moringa leaf decoction on reducing blood glucose levels in diabetes mellitus patients in Sikampuh Village, Kroya District, Cilacap Regency. Method: The method used was a qualitative descriptive method with a case study approach. Results: Based on the research results, administering Moringa leaf decoction to blood glucose levels in diabetes mellitus patients for 7 days was proven to be effective in lowering blood glucose levels. Conclusion: Administering Moringa leaf decoction to diabetes mellitus patients for 7 days can lower blood glucose levels.